'Don't Whine': Sexuality, Adultery and Emancipation in Annie M. G. Schmidt and Harry Bannink's Musical Heerlijk Duurt het Langst (1965). (2nd September 2018) - Thierens, Sanne
Abstract: Annie M. G. Schmidt (1911–1995) and Harry Bannink (1929–1999) are regarded as the founders of the original Dutch musical, having started their tradition with the 1965 production Heerlijk Duurt Het Langst ( Lovely Lasts The Longest ; official English title: Pleasure Pays Off ). With its simple story about a bored married couple with the husband cheating on his wife with his secretary, Heerlijk became a hit. The musical reveals an important expression of uncommonly liberal and progressive values in its treatment of topics such as emancipation, feminism, adultery and sexuality. This essay shows how Heerlijk illustrates the changing dynamics of the position of women and their relationship to sex in the light of the dawning sexual revolution, revealing the gaps between the characters of Marian, the contemporary housewife, Emma, the sexually liberated mistress, and Ido, the cheating patriarch. By placing Heerlijk 's plot and characters into its socio-political historical context, this essay offers an insight into the progressive sensibility of the Netherlands during the early 1960s, as the country prepared for the second feminist wave to arrive.